تنفيذ تكوين البيئة اللغوية في تعليم اللغة العربية لدى طلاب معهد الحمراء الإسلامي مالانج : Implementing and Forming a Language Environment in Arabic Language Teaching for IBS Al-Hamra Students Malang - Fairus Sholeh; Nuril Mufidah (Universitas Ahmad Dahlan, 2022)
Implementing and forming a language environment for IBS Al-Hamra students is very important. Because the majority of them are teaching Arabic at the beginner level, they need to focus entirely on the wealth of vocabulary and application in Arabic in their daily conversations. To achieve these goals, more than learning Arabic in the classroom is required. Accordingly, the school principal collaborated with the supervisor to implement the language environment formation program. This research aims to reveal programs and activities on the implementation formation of language environment at IBS Al-Hamra Malang. Kind this research is qualitative descriptive research to describe the phenomena in the field of study. The researcher used to obtain the data on the method of observation, interview, and documents. The results of this research were the implementation form of a language environment in IBS Al-Hamra based on the state of the formal language environment and the informal language environment that focuses on the assimilation of students' speaking skills. The official language environment at IBS Al-Hamra was through the course of the learning process in the classroom in two classes each week with an estimated time of 60 minutes per class. The informal language environment is related to language activity outside the school. It includes a program of forced communication in Arabic on all student days, vocabulary instruction, group conversation, public speaking, Arabic announcements, and the Arab Festival. In addition, hindrance factors affect the implementation of this language environment, including the teacher, the supervisor, and the learning aids, as well as the supporting elements, which consist of decreased courage of students and their lack of desire to speak Arabic.